Management of Xerostomia in Elderly Patients with Edentulous and Hypertension: Case Report - Ana Medawati; Utami, Myrna Kania (Indonesian Journal of Society Development, 2024)
Xerostomia is defined as a subjective complaint in patients who have a dry mouth. The causes of xerostomia can be classified as systemic or local. Xerostomia can often develop as a side effect of certain medications. Case Report: A 72-year-old male patient came in complaining that his mouth felt dry at night and woke up because his throat felt dry and he had to drink. Patients also feel compelled to drink when swallowing food. The patient can only eat soft foods because all his teeth have been removed and he does not use dentures. The patient has a history of hypertension and is taking amlodipine and Hydrochlorothiazide which are taken once a day in the morning. Discussion: Identification of xerostomia was carried out using the Fox (1987) questionnaire with the results of xerostomia and measurement of saliva flow rate when the patient's indication was 0.56 mL/minute which was not hyposalivation but was still given treatment with GC dry mouth gel for subjective complaints. After the patient used dry mouth gel for 2 weeks, saliva flow rate measurements showed an increase to 0.6 mL/minute and there was improvement in the xerostomia questionnaire. Conclusion: The use of dry mouth gel can reduce subjective complaints and increase the rate of saliva flow in elderly patients who take hypertension drugs in the form of calcium channel blockers and diuretics